The Liberal Script at the Beginning of the 21st Century: Conceptions, Components, and Tensions - Tanja A. Börzel; Johannes Gerschewski; Michael Zürn (Oxford University Press, 2024)
This volume takes stock and understands better what liberal ideas and institutions actually mean in the 21st century and why they are currently so heavily contested. It introduces the concept of “liberal script” to analyze but also problematize liberal thinking as much as its different components, linkages, and the tensions they produce. The edited volume integrates theoretical and methodological perspectives from different disciplines, including political science, sociology, law, history, philosophy, postcolonial studies, and educational science. In demonstrating the theoretical and empirical added value of using “liberal script”, the volume presents a multifaceted and nuanced picture of what is at stake in the challenges of liberalism at the beginning of the 21st century.
Keywords: 300; liberal script; contestations; liberalism; populism; postcolonialism; neoliberalism; democracy; rule of law; human rights; liberal international order